Neuromyelitis optica spectrum disorder in Western China impacts employment and increases financial burden in women - Han, Lin; Hong, Peiwei; Wan, Yang; Cai, Linjun; Shi, Ziyan; Wang, Jiancheng; Lang, YanLin; Zhou, Hongyu (Frontiers in Neurology, 2022)
Background Neuromyelitis optica spectrum disorder (NMOSD) often leads to disability and exerts a heavy toll on the work and life of affected female patients. This study aimed to analyze the current employment situation and economic burden as well as the risk factors for unemployment in female patients with NMSOD. Methods We compared the following unemployment- and employment-related aspects in with NSMOD, which were investigated using questionnaires: the specific impact of NMOSD on work, medical expenses, and factors affecting unemployment. Results We enrolled 351 female patients with NMOSD. More than half (54.1%, 190/351) of participants reported that the disease led to unemployment. The unemployment group was significantly older (46.9 ± 12.1 years vs. 39.3 ± 9.4 years, P = 0.000), had a higher annual recurrence rate (ARR) (0.6 [inter quartile range [IQR]:0.4–0.9] vs. 0.5 [IQR: 0.3–0.8], P = 0.141), and a higher severe disability rate (44.2% vs. 11.2%, P = 0.000) than the employment group. Moreover, unemployed patients had lower education levels. The factors influencing unemployment included low education (junior middle-school or below), age, higher ARR, and severe disability (odds ratio [OR] = 6.943, P = 0.000; OR = 1.034, P = 0.010; OR = 1.778, P = 0.038; and OR = 4.972, P = 0.000, respectively). Medication and hospitalization costs constituted the principal economic burdens. Conclusion The heavy financial burden, employment difficulties, and high unemployment rate are the most prominent concerns of female patients with NMOSD who require more social support and concern.